Los procesos de notificación y su influencia en la recaudación de la Corporación Nacional de Telecomunicaciones en el año 2021 - Yepez Rizo, Washington Xavier (2022)
The National Telecommunications Corporation, or CNT EP for short, is an Ecuadorian public company established on October 30, 2008 to provide Ecuadorians with telecommunications and information and communication technology services. However, this public institution was created by the union of the defunct companies Andinatel S.A and Pacifictel S.A. The mandatory area of the CNT EP is responsible for the recovery of two types of client portfolios: extrajudicial and judicial (or mandatory), all collection processes are regulated by internal regulations such as the Regulation for the Exercise of Mandatory Jurisdiction, and by Ecuadorian legislation. Regarding the recovery of monetary resources, the public body carries out and executes all its collection procedures under the Regulation for the Exercise of Mandatory Jurisdiction and other internal regulations, as well as Ecuadorian legislation. It should be noted that the collection strategy for telecommunications services provided by CNT EP includes the following steps: collection, early portfolio recovery, and extrajudicial and judicial (or mandatory) portfolio recovery.